63.2k views
0 votes
Solve for h.
h/6 − 1 = −3

h =

2 Answers

4 votes

Answer:

h = - 12

Explanation:

Add 1 to both sides of the equation

ℎ/6 − 1 + 1 = − 3 + 1

Simplify

ℎ/6 = − 3 + 1

h/6 = -2

Multiply all terms by the same value to eliminate fraction denominators

6 ⋅ ℎ/6 = 6 ( − 2 )

Cancel multiplied terms that are in the denominator

ℎ = 6 ( − 2 )

Multiply the numbers

ℎ = − 12

User Steve Goodman
by
5.9k points
5 votes

Answer:


h = - 12

Explanation:

1) Add 1 to both sides.


(h)/(6) = - 3 + 1

2) Simplify -3 + 1 to -2.


(h)/(6) = - 2

3) Multiply both sides by 6.


h = - 2 * 6

4) Simplify 2 × 6 to 12.


h = - 12

Therefor, the answer is h = -12.

User Asaf R
by
5.9k points